Decomposing PRC - Japan - US trade: Vertical specialization, ownership, and organizational form - Judith M. Dean; Mary E. Lovely; Jesse Mora (Asian Development Bank Institute (ADBI), 2009)
We used the United States (US) International Trade Commission's uniquely detailed 1995-2007 PRC customs data to better understand the pattern of trade between the People's Republic of China (PRC) and its two largest trading partners, Japan and the US. Our review finds that only a small share of these flows can be characterized as arm's length, one-way trade in final goods. Instead, we found extensive two-way trade, deep vertical specialization, concentration of trade in computer and communication devices, and a prominent role for foreign-invested enterprises. While these characteristics define both bilateral relationships, important differences between the two pairs do emerge, suggesting that trade costs influence the method by which multinational firms choose to integrate their production with the PRC. Consequently, we argue that dialogue on East Asian trade liberalization should include the possibility of significant production gains for the US from its inclusion in any regional agreements.
Keywords: F14; F15; 330